Formation of safe behavior of schoolchildren in daily activities through fire-applied sports - Vorobyov R.S.; Ponomarev V.V.; Zhernakov D.V.; Ukolov A.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to substantiate and develop program content based on students’ classes in fire-applied sports in physical education at school as a means of developing safe behavior in children and adolescents in everyday activities and adapt it in practice. Methods and structure of the study. A theoretical analysis of the content of physical education programs implemented today in general education institutions, an analysis and synthesis of methodological literature on fire-applied sports were carried out, and its relevance in the physical education of schoolchildren was determined. Based on the collected analytical material, an experimental physical education program for children in grades 5-11 has been developed, the content of which includes means, methods and forms of practicing fire-fighting sports at school. Results and conclusions. Conducting additional classes in a general education institution using fire-fighting sports, according to the developed program, helps students develop an adequate level of response to critical life situations, strengthens knowledge about safe behavior, develops skills in overcoming extreme situations, and increases interest in classes fire-applied sports, develop moral-volitional and moral-psychological qualities of the individual. The implementation of this program in secondary schools will allow children to instill knowledge and skills in the field of fire and rescue sports. Develop the necessary skills for safe behavior in everyday life in the face of various dangers.